2002
DOI: 10.1093/alcalc/37.4.347
|View full text |Cite
|
Sign up to set email alerts
|

CONTRIBUTION OF FRONTAL CEREBRAL BLOOD FLOW MEASURED BY 99mTc-BICISATE SPECT AND EXECUTIVE FUNCTION DEFICITS TO PREDICTING TREATMENT OUTCOME IN ALCOHOL-DEPENDENT PATIENTS

Abstract: Inhibition and working memory deficits, associated with low levels of CBF in the medial frontal gyrus, are related to the difficulty of maintaining short-term abstinence from alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
95
2
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 58 publications
6
95
2
4
Order By: Relevance
“…Similarly to Noël et al (2001Noël et al ( , 2002; see also Ratti et al 2002), we observed that ALC exhibited working memory abnormalities. The results of the alpha-span task show that ALC's ability to store information in working memory (measure the span size and the score of direct recall condition) remained normal, but the ability to manipulate the information stored (measured by the alphabetical recall condition) was impaired.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly to Noël et al (2001Noël et al ( , 2002; see also Ratti et al 2002), we observed that ALC exhibited working memory abnormalities. The results of the alpha-span task show that ALC's ability to store information in working memory (measure the span size and the score of direct recall condition) remained normal, but the ability to manipulate the information stored (measured by the alphabetical recall condition) was impaired.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, abnormal motivational properties of alcohol and/or impaired prepotent response inhibition may lead to loss of control of alcohol use and to alcohol relapse (Noël et al 2002;Cox et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathological observations demonstrated alcoholismrelated neuronal loss in prefrontal association-cortex, hypothalamus, and cerebellum (64,65). Frontal dysfunction in alcoholism has been demonstrated by neuropsychological investigations (66)(67)(68)(69)(70)(71) and by metabolic (20), cerebral blood flow (72,73), and functional MRI (74) studies. Brain structural changes become more prominent with aging (17,21,35), and alcoholism can exaggerate age-related volumetric reductions (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol-dependence has been associated with memory compromise, a compromise that has been observed for working memory [1][2][3][4][5], for memory for verbal or nonverbal stimuli [6][7][8], and for source memory, i.e., the ability to remember the context in which an event occurred [9,10]. Interestingly, autobiographical memory, or memory for personal experiences, has been also found to be compromised in alcohol-dependence.…”
Section: Introductionmentioning
confidence: 99%